Colonoscopic Examination, Histopathological findings and medical management of Lymphocytic-Plasmacytic colitis in a Dog - Priya, S. Vishnu; Kumar, G. Senthil; kumar, E. Venkatesa; Senthilvel, K. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Colitis is defined as the inflammation of colon and is the most common cause of significant bowel diarrhea. Any colon damage may results in inflammation of colon and disturbances in both absorption and motility. In this case, a male German Shepherd was presented with the history of bloody diarrhea for the past one week, tenesmus and frequent voiding of small volume of faeces. Hemato-biochemical analysis revealed slight lymphocytopenia, hypoproteinemia and hypoalbuminemia. On physical examination, animal showed pain on palpation of abdomen and digital rectal examination with hematochezia. Colonoscopy was performed. Histopathological assessment of intestinal biopsy remains the gold standard for diagnosis of intestinal inflammation. The usefulness of endoscopic examination for the diagnosis and treatment of colitis in dogs was determined in this study.